DETERMINATION OF MELDONIUM, γ-BUTYROBETAINE, AND CARNITINE IN BLOOD PLASMA BY HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY WITH MASS-SELECTIVE DETECTION - P. N. Sorokoumov; E. I. Savelieva; G. V. Karakashev; V. A. Kopeikin; A. S. Radilov (Разработка и регистрация лекарственных средств, 2019)
A procedure for simultaneous quantitative determination of meldonium, L-carnitine, and γ-butyrobetaine in blood plasma by high-performance liquid chromatography with mass-selective detection and the isotopically labeled d9L-carnitine as internal standard is proposed. An algorithm for constructing calibration plots for the quantitation of biogenic plasma components (L-carnitine, and γ-butyrobetaine) is developed. The procedure is validated for the concentration range from 0,05 to 20 µg/cm3 and applied in a pharmacometabolomic study of blood plasma on protracted administration of meldonium as a monopreparation and as a complex with L-carnitine.